2023
DOI: 10.3390/ijms24020952
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complex HB324 Induces Apoptosis via Mitochondrial Pathway with an Upregulation of Harakiri and Overcomes Cisplatin Resistance in Neuroblastoma Cells In Vitro

Abstract: Ruthenium(II) complexes with N-heterocyclic carbene (NHC) ligands have recently attracted attention as novel chemotherapeutic agents. The complex HB324 was intensively studied as an apoptosis-inducing compound in resistant cell lines. HB324 induced apoptosis via mitochondrial pathways. Of particular interest is the upregulation of the Harakiri resistance protein, which inhibits the anti-apoptotic and death repressor proteins Bcl-2 (B-cell lymphoma 2) and BCL-xL (B-cell lymphoma-extra large). Moreover, HB324 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Ruthenium complex HB324 has been shown to effectively inhibit the proliferation of leukemia cells in a dose-dependent manner. At a concentration of 1 µM, HB324 caused 100% proliferation inhibition, indicating its potential as an effective anti-proliferative agent [16].…”
Section: Discussionmentioning
confidence: 98%
“…Ruthenium complex HB324 has been shown to effectively inhibit the proliferation of leukemia cells in a dose-dependent manner. At a concentration of 1 µM, HB324 caused 100% proliferation inhibition, indicating its potential as an effective anti-proliferative agent [16].…”
Section: Discussionmentioning
confidence: 98%
“…The millimeter dimensions of the resulting inhibitory zones were used as a benchmark for anti‐microbial activity. As a negative control, solvent controls (DMSO) were included in all experiments [45] . The investigated compounds were dissolved in DMSO, which showed no inhibitory zone, confirming that it has no effect on the development of the observed bacteria and fungi.…”
Section: Methodsmentioning
confidence: 94%
“…substituted with methyl on benzimidazole ring was found to efficiently activate Harakiri (HRK), a proapoptotic protein from the Bcl-2 family that interacts with and inhibits the antiapoptotic and death-repressor proteins Bcl-2 and Bcl-xl, thereby promoting apoptosis. 68 Furthermore, the authors also demonstrated that Rh(I)-NHC complex 5, which contains a naphthalimide moiety, can induce apoptosis in Nalm-6 cells through the mitochondrial pathway.…”
Section: Target Bcl-2 Familymentioning
confidence: 97%